Step by step PHACO [CD] - Agarwal, Sunita; Agarwal, Athiya; Agarwal, Amar (New Delhi : Jaypee Brothers Medical Publishers, 2006)
Phaco es lectura prescrita para todos los involucrados en la rutina de la cirugía de cataratas. Con dos CD ROM interactivos.
Contents 1. Gas forced infusion 2. No Anesthesia Cataract Surgery with the Karate Chop Technique 3. Phaco in Subluxated Cataracts 4. Mature Cataracts 5. Small Pupil Phacoemulsification and others more...
No necesita instalación previa
Con dos CD ROM interactivos
Incluye bibliografía
Keywords: CATARACT SURGERY -- AUDIOVISUAL; CATARATAS -- AUDIOVISUAL; FACOEMULSIFICACIÓN